Decoding the mojo of plant-growth-promoting microbiomes. (August 2021) - Mulani, Rinkal; Mehta, Krina; Saraf, Meenu; Goswami, Dweipayan
Abstract: Farmers, so-called the father of land, have a tremendous responsibility to feed the world. The demand for agricultural yield is constantly surging, and the resources that provide this agricultural yield is limited. This imbalance has forced farmers to treat their crops with chemicals to improve yield. These chemical substances are broadly classified as chemical fertilizers and chemical pesticides. A century ago, these chemicals were thought to be a boon for farmers, and the golden age of chemistry was parallel being witnessed in agriculture. The constant use of these chemicals in soil over several years has ultimately exposed its dark side, as its detrimental impact is well spread from diminishing farmer-friendly nematodes like earth warms to a culprit in causing cancer in vertebrates. Therefore, an alternative to these chemicals is inevitable to be provided in the agriculture system for sustainable development. The answer to this hurdle is obtained in the form of the microbiome of soil that interacts with plants and helps it by symbiotic associations. Some members of microbes found in this microbiome are to be identified that has a positive impact on plant growth and is apotheosized to be used as a biological alternative to chemical fertilizers. Such microbes are broadly classified as Plant-Growth-Promoting Rhizobacteria (PGPR) and Plant-Growth-Promoting Fungi (PGPF) microbiome. The association of such Phyto-friendly microbes is well characterized by researchers globally and is depicted in this review. Highlights: Soil Microbiome include microbes of Caulosphere, rhizosphere, Phyllosphere and endosphere. Rhizosphere and Phyllospheric microorganisms enhance plant productivity. Actinobacteria, Bacteroidetes, Firmicutes and proteobacteria as PGPR. Role of PGPR in combating environmental stresses experienced by plants.